ENGLISH TEACHING IN SOCIAL AND CULTURAL CONTEXTS: LANGUAGE TEACHERS AS CULTURAL MANAGERS - Suryani, Adi; Soedarso, Soedarso; Diani, Kurnia Tri; Rosmawati, Rosmawati (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
Teaching English language can be dilemmatic since English teachers should introduce foreign culture and sustain their own students culture. Todays students are the future leaders. Thus, it is vital for the English teachers to introduce global culture and local-national culture. This study aims to explore our own experiences at school and higher education levels, in managing culture in our EFL practices: which cultural elements should be sustained, how, why and what the challenges are. The data are collected from our experience-based reflection. The study indicates that English language teachers play a meta-role as cultural managers. They are selecting, infusing, inventing ways to teach culture through various approaches: materials, social interaction, classroom routines and artefacts. However, this process can be impeded by the disruptive technology, students, teachers own and organizational factors. Thus, this cultural managing role is influenced by organization, technology, learners adaptation process and teachers own cultural awareness and understanding.